THE MECHANISM OF PROTECTION OF INTELLECTUAL PROPERTY IN A COMMON ECONOMIC SPACE - Жатканбаев, Е. Б.; Кудайберген, Ж. К. (Journal of Economic Research & Business Administration, 2015)
This article analyzes process of formation and modern situation of intellectual property, as one of forms of a private property in Common Economic Space (CES) countries. Represented the agreements of CES’s partia-pating countries as the mechanism of intellectual property’s defence and disadvatages.